The Motive of the Ban on Cow Slaughter by Sunan Kudus and its Relevance to Strengthening Religious Moderation - Winarto Winarto; Ahmad Shuhada; Adika Arifin Matlawi; Nazwa Aulia Fitriyana (Muttaqien, 2024)
Islamization in Java during the 15th-16th centuries AD proceeded peacefully without warfare. Ja'far Shadiq, popularly known as Sunan Kudus, was a wali who contributed significantly to the spread of Islam in Java in the 16th century AD. Sunan Kudus issued a fatwa to the people of Kudus at that time, prohibiting the slaughter of cows. This fatwa seemed contrary to Islamic teachings, which permitted the slaughter of cows for consumption or religious sacrifice. Interestingly, this fatwa is still practiced by the people of Kudus today. Nowadays, some Muslims, especially textualists, question this prohibition because it is considered inconsistent with Islamic teachings. This article aims to reassess the true intention behind the fatwa so that all parties can address it wisely. This study uses qualitative methods by collecting field and written data from books and journals. This research concludes that the fatwa prohibiting the slaughter of cows by Sunan Kudus cannot be separated from the social, religious, and cultural context of its time. Second, it was part of a tolerant da'wah strategy he implemented to continue the process of Islamization. Third, the prohibition was a form of respect for the traditions and beliefs of other religions, not an absolute and permanent legal ban, thus allowing for the slaughter of cows at the right time and place. The results of this study can contribute to efforts to reaffirm that respecting local traditions is a critical point to strengthen the paradigm of religious moderation.